PELAKSANAAN KEBIJAKAN DAN PENILAIAN PENGGUNAAN APD (ALAT PELINDUNG DIRI) OLEH DOKTER DAN BIDAN DI RUANG BERSALIN DAN NIFAS RSU PKU MUHAMMADIYAH YOGYAKARTA UNIT I TAHUN 2014/2015 - Nia Supiana; Supriyatiningsih Supriyatiningsih (Universitas Muhammadiyah Yogyakarta, 2015)
Background: Hospital is a place for taking care of the patients where there are many kinds of disease there. Disease caused by infection is one of disease that can be found in hospital. It can be the mild one or the severe one. Therefore, it can spread from one patient to the other patients. Besides that, the workers also can be infected since their job required them to having a contact with the infection agent. The General hospital of PKU Muhammadiyah Yogyakarta Unit 1 has formed the Komite Pencegahan dan Pengendalian Infeksi (KPPI) or Committee of Prevention and Restraint of Infection since 2012, this committee has made a policy related to universal precautions which giving protection to medical staff, patients, and patients’ families. Methods: In collecting the data, this research used mixed method with concurrent triangulation strategy design and cross-sectional approach. The population of this research is doctors in delivery and postpartum room and the members of KPPI. The total of the population is 30 people. In analyzing the data, the writer used logistic regression. The resources were taken from some related books, journals, articles, and research from several media. Results and Discussion: The result of this research showed that the degree of compliance of doctors and midwives in using PPE (Personal Protective Equipment) in postpartum room (92.9%) was higher than the using of PPE in the delivery room (76.9%). This implementation/compliance is influenced by disposition factors/attitude (ρ = 0.000 <0.05) and the structure of bureaucracy (ρ 0,000 <0.05), while the variable of communication (ρ=0,164 > 0,05) and resource (ρ=0,431 > 0,05) do not influence on the implementation of the use of PPE. Conclusions and Recommendations: The implementation of the use of PPE in the delivery and postpartum room is still not performing well and the evaluation process was still not optimal. The hospital is expected to improve the supervision of the head room. Moreover, the implementation of SOP (Standard Operational Procedure) on the universal Guidelines for Vigilance Implementation should be conducted especially the use of PPE in delivery and postpartum room.